Lyrical “I” as a Prophetic Subject in the Poem “Alang-Alang” by Abdul Wachid B.S. - Rabbani, Ilham; Hangganararas, Hatindriya (Journal Corner of Education, Linguistics, and Literature, 2024)
The poem “Alang-Alang” by Abdul Wachid B.S. explores the struggle of the lyrical “I”, representing the Indonesian people, to break free from the shackles of the New Order political regime. By focusing on the voice of the lyrical “I”, this study aims to dismantle the prophetic structure of the poem by analyzing the aspects of humanization, liberation, and transcendence within it. Kuntowijoyo’s concept of prophetic literature serves as the primary analytical framework, employing a qualitative-descriptive method. The findings of this study are as follows: first, the aspect of humanization is depicted through the lyrical “I”s efforts to challenge the consciousness of power, aiming to restore the people’s conscience to its rightful place; second, the aspect of liberation is demonstrated through attempts to free the people from the constraints imposed by the New Order, including physical violence and ideological control; and third, the aspect of transcendence is reflected in the lyrical “I” awareness of God’s power (Sang Hyang or Allah Swt.), which surpasses human capabilities. This context establishes the lyrical “I” in the poem “Alang-Alang” as meeting the criteria of a prophetic subject in literary texts.